On the Road: The Appeal of Buddhism to Travellers. Issue 2 (2nd July 2016) - Veidlinger, Daniel
Abstract: Buddhism has been associated with travel and transportation since its inception. The Buddha himself led a peripatetic life wandering from town to town preaching his dharma, and King Aśoka sent missionaries travelling far and wide. Travelling merchants were the most prominent early converts to Buddhism and their prominence in the religion continued for a long time. This article explores the importance of travel in the acceptance of Buddhist ideas, and will show that the changes in worldview undergone by one travelling from place to place, encountering along the road different ways of thinking, dressing, speaking and living are likely to foster in such a person an interest in some of the seminal ideas embodied in Buddhism. The psychological effects of travel force people to wrestle with their previously accepted local truths, drawing them instead to Buddhism's universal outlook, its teaching of compassion for all beings and rejection of culturally specific social restrictions.